Outdoor thermal performance of urban development patterns in Greater Adelaide since the late 19th century - Yue Liu; Yuhan Zhang; Ehsan Sharifi; Yaqiao Liu; Qiqi Liu; David Kroll (Scientific Reports, 2024)
Abstract Extreme heat events have become more common and more severe during summer than ever before as a result of the warming climate in Australia. The impact of urban morphology and green coverage on outdoor thermal comfort has been the subject of extensive research, however, their link to suburban developments of different historic periods is still underexplored. This paper investigates and compares the outdoor thermal performance of ten suburban areas constructed since the late nineteenth century in Greater Adelaide, which were built to different planning ideals and concepts of their time. Microclimate models of two precedents for five development eras were constructed in ENVI-met, validated with site data related to a recent heatwave event in 2023, and then used to facilitate further investigation of the impact of development patterns on outdoor thermal comfort. This study examines how these urban patterns perform in scenarios of varying development intensity and greenery ratio. In these case studies, the distance between buildings, streets’ spatial ratio and green coverage has a significant impact on the thermal environment. The results underline the impact of solar exposure on outdoor thermal performance even in lower-density suburban areas. Some of the outcomes of the study are counter-intuitive to conventional assumptions about urban design typologies. In this comparison, for example, one of the “green” model garden city developments did not perform as well as denser 19th-century suburbs. The results can support better decision-making for future urban planning in Australia and other regions with similar climate conditions. The study shows that real performance does not always align with stated green ambitions and, urban design should consider and evaluate heat mitigation through evidence-based testing to achieve real green development.